Predictors of fatigue progression in long COVID among young people - Elias Myrstad Brodwall; Joel Selvakumar; Lise Beier Havdal; Silke Sommen; Lise Lund Berven; Erin Cvejic; Vegard Bruun Bratholm Wyller; Maria Pedersen (Brain, Behavior, & Immunity - Health)
Long COVID, or post-COVID-19 condition (PCC), has emerged as a significant health concern, with fatigue being the most prevalent persistent symptom among young people. However, research on predictors of fatigue progression in young populations is limited. This study aimed to investigate factors during acute SARS-CoV-2 infection that could predict fatigue progression between six and 12 months post-infection in a cohort of young people with chronic fatigue following COVID-19. Data from the Long-Term Effects of COVID-19 in Adolescents (LoTECA) project were analyzed. A total of 93 participants (mean age 18.5 years, 84 % female) with chronic fatigue at six months, completed the 12-month follow-up. Multivariate analyses identified non-European ethnicity, higher interferon gamma (IFN-γ) levels, and lower RR-interval (higher resting heart rate) during acute infection as significant predictors of fatigue progression from six to 12 months. These three factors explained 21 % of the variance in the fatigue score, highlighting the importance of ethnicity, immune response, and autonomic function in the trajectory of long COVID fatigue. Early identification and targeted interventions, particularly for ethnic minorities and those with specific immune or autonomic markers during acute infection, may be helpful in reducing long-term fatigue. Further research is needed to explore treatment strategies for affected young populations.